2007
DOI: 10.1017/s0305000906007835
|View full text |Cite
|
Sign up to set email alerts
|

Joint attention and word learning in Ngas-speaking toddlers in Nigeria

Abstract: This study examines infants' joint attention behavior and language development in a rural village in Nigeria. Participants included 8 younger (1;0 to 1;5, M age = 1;2) and 8 older toddlers (1;7 to 2;7, M age = 2;1). Joint attention behaviors in social interaction contexts were recorded and coded at two time points 6 months apart. Analyses revealed that these toddlers were producing more high level joint attention behaviors than less complex behaviors. In addition, the quality and quantity of behaviors produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
66
3
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 31 publications
3
66
3
1
Order By: Relevance
“…However, Childers et al (2007) also found that joint attention behaviours were just as closely linked to lexical development -both noun and verb comprehension and production -as in previous studies in developed regions. Although parent and caregiver joint attention behaviours may be different in this culture, this does not seem to affect the relationship between joint attention and vocabulary.…”
Section: Early Vocabulary and Related Skillssupporting
confidence: 66%
See 3 more Smart Citations
“…However, Childers et al (2007) also found that joint attention behaviours were just as closely linked to lexical development -both noun and verb comprehension and production -as in previous studies in developed regions. Although parent and caregiver joint attention behaviours may be different in this culture, this does not seem to affect the relationship between joint attention and vocabulary.…”
Section: Early Vocabulary and Related Skillssupporting
confidence: 66%
“…Two research groups (Alcock, Rimba, Abubakar, & Holding, 2005;Childers, Vaughan, & Burquest, 2007) have examined the composition of early vocabulary among children in the region learning Kiswahili and Kigiriama, and Ngas, spoken in Kenya and Nigeria respectively. Typically nouns predominate in early production vocabulary, and this is true across many languages studied to date (Bornstein et al, 2004).…”
Section: Early Vocabulary and Related Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have shown that from the first words onward there are language-specific differences in the composition of the early vocabulary, and that there is no conceptually based universal noun preference in terms of the first words uttered (Childers et al, 2007;Tardif et al, 2008;Bornstein et al, 2004) nor any universal noun bias in terms of early frequencies (Tardif, 1996 ;Tardif et al, 1997;Choi & Gopnik, 1993;Brown, 1998 ;de Léon, 1999). The absence of such a universal bias means that we cannot explain the high noun-to-verb ratio in the younger children in Chintang by appeal to a conceptual basis, independent of the specific language that is acquired.…”
Section: Discussionmentioning
confidence: 99%